STRATEGI KEPALA SEKOLAH DALAM MENGIMPLEMENTASIKAN PENDIDIKAN KARAKTER - Kasnawi Kasnawi (Universitas Pendidikan Indonesia, 2021)
This study examines the problem of the principal's strategy in implementing character education. Research aims to: a) Knowing and getting information about socialization, capacity building, implementation and cooperation, as well as monitoring evaluating the implementation of religious character education, discipline, social care, and , b) knowing and getting information about factors and inhibitors of the principal in the implementation of character education. The method used in this research is descriptive method through qualitative approach. The number of participants as many as 4 people are principal, teachers, and 2 students. Data collection techniques are conducted with interviews and documentation studies. The results showed that the principal a) socialized character values through meetings, small talk, and lectures to children, b) held teacher training c) cooperated with all teacher and staff personnel , foundations, school committees, parents' representatives, local residents, Zakat Umat Controllers (PZU), and the National Committee for the Palestinian People (KNRP), d) monitoring and evaluation by principals and teachers. Factors for principals are cooperation, commitment, motivation, support and a conducive, safe and peaceful environment / climate. While the inhibiting factors are time, lack of cooperation, bad environment, facilities and infrastructure.